The natural gift in Rousseau’s politics and educational theory - Tsampazis, Nick (Dia-noesis: A Journal of Philosophy, 2024)
Rousseau’s theoretical treatment of natural talent exhibits two distinct tendencies. The first draws inspiration from the primitive, wholly natural existence of early humans before the advent of civilization. In contrast, the second tendency is grounded in the concept of nature as an ontological foundation for authenticity within the context of alienated civilization of his time. The first perspective is defined by suspicion towards natural talent because it runs counter to the model of elementary egalitarian naturalism inherent in the genuine state of nature. In this view, any exceptional abilities or talents disrupt the inherent equality of primitive existence. Conversely, the second tendency celebrates natural talent as a rare expression of untouched nature within the confines of civilized society. Such talents possess the potential for liberation and redemption, serving as a counterbalance to the alienation that pervades modern life.